English and the Indian short story: essays in criticism - Mohan Ramanan; Mohan Ramanan; Sailaja P (New Delhi : Orient Longman, 2000)
Contributed articles presented at the National Seminar on "English and the Indian Short Story" held in August 1994 at the Dept. of English, University of Hyderabad.
Keywords: Stories Indian English Criticism; Stories English Criticism; Literature Indian English; Literature